Transformation in the Thai land scape: an emerging role for social forestry in Rural Development Programmes - Thomas David E.
Recent decades have brought profound changes in the patterns of land use in the Kingdom of Thailand. While various studies to document and analyse these changes and their implications for the future, it is already clear that they reflect a complex set of powerful forces at work in Thai society. This article seeks to highlight various processes, some of the responses to emerging problems associated with changing land-use patterns, and the need for effective inter agency efforts in developing social forestry programmes which meet the needs of local communities. Reproduced.
Keywords: Land Use, Urban -- Thailand; Forests -- Thailand; Rural Development -- Citizen Participation -- Thailand